2006
DOI: 10.1182/blood-2005-12-008755
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural pesticide use and risk of t(14;18)-defined subtypes of non-Hodgkin lymphoma

Abstract: Pesticides have been specifically associated with the t(14;18)(q32;q21) chromosomal translocation. To investigate whether the association between pesticides and risk of non-Hodgkin lymphoma (NHL) differs for molecular subtypes of NHL defined by t(14; 18) status, we obtained 175 tumor blocks from case subjects in a population-based case-control study conducted in Nebraska between 1983 and 1986. The t(14;18) was determined by interphase fluorescence in situ hybridization in 172 of 175 tumor blocks. We compared e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(125 citation statements)
references
References 37 publications
6
112
0
5
Order By: Relevance
“…In contrast, Chiu et al 52 analyzed pooled data from 3 case-control studies, and found little evidence of heterogeneity in the association of agricultural exposures with NHL risk between those who did and did not have a family history of cancer. Chang et al 475 observed that a family history of hematopoietic cancer did not modify the association of NHL risk with UV radiation exposure, alcohol consumption, smoking status, dietary intake of red meat, dairy products, fruits and vegetables, or coffee or use of certain medications.…”
Section: Interactions With Environment and Lifestyle Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Chiu et al 52 analyzed pooled data from 3 case-control studies, and found little evidence of heterogeneity in the association of agricultural exposures with NHL risk between those who did and did not have a family history of cancer. Chang et al 475 observed that a family history of hematopoietic cancer did not modify the association of NHL risk with UV radiation exposure, alcohol consumption, smoking status, dietary intake of red meat, dairy products, fruits and vegetables, or coffee or use of certain medications.…”
Section: Interactions With Environment and Lifestyle Factorsmentioning
confidence: 99%
“…Zhu et al 479 observed a significantly elevated risk of NHL in men who reported a family history of lymphoma (OR 5 3.0, 95% CI: 1.7-5.2) and hematologic malignancies (OR 5 2.0, 95% CI: 1.2-3.4). Chiu et al 52 reported increased risks of NHL in men with a family history of hematopoietic (OR 5 2.7, 95% CI: 1.9-3.7) and nonhematopoietic (OR 5 1.5, 95% CI: 1.3-1.8) cancer among first-degree relatives. Cases who were translocation t(14;18)-negative were significantly more likely to report a first-degree family history of hemolymphatic cancer than controls (OR 5 2.4, 95% CI: 1.4-3.9) in a population-based case-control study of participants enrolled in the FARM study.…”
Section: Family History and Genetic Factors Family Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental exposure to some chemicals, ultraviolet light, dietary factors, family history, immune dysfunction, immune stimulation, and viral infection, have all been associated with the risk for NHL, but the results remain inconsistent. In addition to exogenous exposures, individual genetic susceptibility may be important in the pathogenesis of NHL (Chiu et al, 2004;Hartge, 2004;Grulich et al, 2007). Although this would not explain the rising incidence of NHL per se, genetic variants could interact with environmental exposures and thereby contribute to lymphomagenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Among 121 216 women participating in the prospective California Teachers Study, NHL risk varied by type of haematopoietic malignancy and gender of the relative. Evidence from epidemiologic studies shows that the risk of nonHodgkin's lymphoma (NHL) is increased by approximately twofold for individuals with a first-degree family history (parent, sibling or child) of haematopoietic malignancy (Pottern et al, 1991;Zhu et al, 1998;Chiu et al, 2004;Altieri et al, 2005;Chang et al, 2005;Goldin et al, 2005;Wang et al, 2007). However, the underlying mechanisms are poorly understood.…”
mentioning
confidence: 99%